REDUÇÃO DE SÓLIDOS ORIUNDO DA CO-DIGESTÃO ANAERÓBIA DOS DEJETOS DE BUBALINOS E SUÍNOS - SANTOS, Marrony Gonçalves Pires dos; BEZERRA, Thaís dos Santos2 (thaysantos09876@gmail.com); CORREA, Jonas de Sousa; SANTOS, Tânia Mara Baptista dos (ANAIS DO ENIC, 2023)
-